RESPONSIBLITAS PIMPINAN UIN MAULANA MALIK IBRAHIM DALAM UPAYA MEMBERIKAN AKSES TERHADAP DIFFERENT ABILITY PERSPEKTIF UU NO. 8 TAHUN 2016 TENTANG PENYANDANG DISABILITAS - Erfaniah Zuhriah (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2016)
This study discusses the response of the leadership of UIN Maulana Malik Ibrahim in an effort to provide access to persons with disability perspective of law No. 8 year 2016 About persons with Disability.This type of research is empirical research, located on campus 1 UIN Maulana Malik Ibrahim of Malang. The research approach used is the juridical sociological approach, statue approach and conceptual approach. Types and sources of data consists of primary data, secondary data, and tertiary data material. Primary data collection techniques by interviews and observations directly in the field, secondary data by library study and tertiary data obtained from General dictionary, legal dictionary, ensiclopedia etc. Technique of data analysis is done using qualitative jurirical analysis method that focused on